Identification of asthma phenotypes based on extrapulmonary treatable traits. Issue 1 (21st January 2021) - Freitas, Patricia Duarte; Xavier, Rafaella França; McDonald, Vanessa Marie; Gibson, Peter Gerard; Cordova-Rivera, Laura; Furlanetto, Karina Couto; de Oliveira, Joice Mara; Carvalho-Pinto, Regina Maria; Cukier, Alberto; Stelmach, Rafael; Carvalho, Celso Ricardo Fernandes
Asthma is a heterogeneous and complex disease, and a description of asthma phenotypes based on extrapulmonary treatable traits has not been previously reported. The objective of this study was to identify and characterise clusters based on clinical, functional, anthropometrical and psychological characteristics in participants with moderate-to-severe asthma. This was a cross-sectional multicentre study involving centres from Brazil and Australia. Participants (n=296) with moderate-to-severe asthma were consecutively recruited. Physical activity and sedentary time, clinical asthma control, anthropometric data, pulmonary function and psychological and health status were evaluated. Participants were classified by hierarchical cluster analysis and the clusters compared using ANOVA, Kruskal–Wallis and Chi-squared tests. Multiple logistic and linear regression models were performed to evaluate the association between variables. We identified four clusters: 1) participants with controlled asthma who were physically active; 2) participants with uncontrolled asthma who were physically inactive and more sedentary; 3) participants with uncontrolled asthma and low physical activity, who were also obese and experienced anxiety and/or depression symptoms; and 4) participants with very uncontrolled asthma who were physically inactive, more sedentary, obese and experienced anxiety and/or depression symptoms. Higher levels of sedentary time, female sex and anxiety symptoms were associated with increased odds of exacerbation risk, while being more active showed a protective factor for hospitalisation. Asthma control was associated with sex, the occurrence of exacerbation, physical activity and health status. Physical inactivity, obesity and symptoms of anxiety and/or depression were associated with worse asthma outcomes, and closely and inextricably associated with asthma control. This cluster analysis highlights the importance of assessing extrapulmonary traits to improve personalised management and outcomes for people with moderate and severe asthma. Cluster analysis based on extrapulmonary treatable traits in people with moderate-to-severe asthma indicates that physical inactivity, higher levels of sedentary time, symptoms of anxiety and depression, and obesity are associated with worse outcomes .https://bit.ly/2ATv1Ce